Effects of Purple and Green-Colored Bottle Traps on Captures of Ambrosia Beetles in Ornamental Nurseries - Ramkumar Govindaraju; Shimat V. Joseph (Agronomy)
The granulate ambrosia beetle, Xylosandrus crassiusculus (Motschulsky), and the black stem borer, Xylosandrus germanus (Blandford), are important pests in ornamental nurseries. The effects of monitoring trap color in capturing adult X. crassiusculus and X. germanus are mixed in the literature. Because the colorless bottle trap is commonly used to monitor ambrosia beetles in ornamental nurseries, it is unclear if adding purple or green, commonly used for collecting cerambycids and buprestids, would improve adult X. crassiusculus and X. germanus captures. Thus, the objective of this study was to compare the effect of purple or green-colored bottle traps with colorless bottle traps on captures of adult X. crassiusculus and X. germanus in ornamental nurseries. In 2023 and 2024, experiments were conducted using bottle traps baited with AgBio low-release ethanol lure (LR ethanol lure). Adding purple or green to the bottle trap did not improve captures of adult X. crassiusculus and X. germanus. Adult X. germanus captures were reduced in the green-bottle trap than in the colorless trap. The purple bottle trap did not collect more numbers of adult X. crassiusculus and X. germanus than the colorless bottle trap with LR ethanol lure. This suggests that adding purple or green to bottle traps did not provide additional value in monitoring ambrosia beetles in ornamental nurseries for management decisions.